Eugene O'Neill. - Gassner, John, 1903-1967 (University of Minnesota pamphlets on American writers, 1965)
Eugene O'Neill - American Writers 45 was first published in 1965. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.